2017
DOI: 10.1126/science.aal3231
|View full text |Cite
|
Sign up to set email alerts
|

Pcdhαc2 is required for axonal tiling and assembly of serotonergic circuitries in mice

Abstract: Serotonergic neurons project their axons pervasively throughout the brain and innervate various target fields in a space-filling manner, leading to tiled arrangements of their axon terminals to allow optimal allocation of serotonin among target neurons. Here we show that conditional deletion of the mouse protocadherin α (Pcdhα) gene cluster in serotonergic neurons disrupts local axonal tiling and global assembly of serotonergic circuitries and results in depression-like behaviors. Genetic dissection and expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
154
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(163 citation statements)
references
References 48 publications
9
154
0
Order By: Relevance
“…For example, recent studies have shown that unique interaction of PcdhγC3 with Axin1 inhibits Wnt signaling [70]. In general, a more complex picture of Pcdh gene expression is emerging, in which distinct Pcdh gene clusters are expressed in different types of neurons, and the alternate and C-type isoforms are differentially expressed during the development of neural circuits [4, 16, 60]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies have shown that unique interaction of PcdhγC3 with Axin1 inhibits Wnt signaling [70]. In general, a more complex picture of Pcdh gene expression is emerging, in which distinct Pcdh gene clusters are expressed in different types of neurons, and the alternate and C-type isoforms are differentially expressed during the development of neural circuits [4, 16, 60]. …”
Section: Discussionmentioning
confidence: 99%
“…To determine if the Pcdh-cluster affected MGE/POA-derived cIN survival, constitutive Pcdh-cluster knockout mice were crossed to Nkx2-1 Cre ;Ai14 mice (Figure 7a). Similarly to the deletion of Pcdh-cluster, mice carrying a deletion of the entire Pcdhcluster, are viable, fertile and of a normal weight (Figure C, top graph) (Chen et al 2017) The density of cIN was similar between mice lacking -Pcdhs and controls ( Figure 7C). The above results indicate that unlike the Pcdh-γ cluster that is essential for the regulation of cIN elimination, the function of -or -Pcdhs is dispensable for the survival of MGE/POA-derived cINs.…”
Section: Alpha and Beta Pcdhs Do Not Impact Cin Survivalmentioning
confidence: 85%
“…Our model assumes no self-avoidance or biological feedback signals that depend on fiber density. Several factors have been reported to control the growth of distribution of serotonergic fibers, but this research has been heavily influenced by the notion that orderly distribution cannot be achieved without tight biological control (see, for example, Chen et al (2017)). The simulation results provide evidence that a considerable degree of self-organization can be achieved with simple assumptions, but it does not rule out these factors.…”
Section: Discussionmentioning
confidence: 99%